Analysis of Magnaporthe oryzae Genome Reveals a Fungal Effector, Which Is Able to Induce Resistance Response in Transgenic Rice Line Containing Resistance Gene, Pi54 - Ray, Soham; Singh, Pankaj K.; Gupta, Deepak K.; Mahato, Ajay K.; Sarkar, Chiranjib; Rathour, Rajeev; Singh, Nagendra K.; Sharma, Tilak R. (Frontiers in Plant Science, 2016)
Rice blast caused by Magnaporthe oryzae is one of the most important diseases of rice. Pi54, a rice gene that imparts resistance to M. oryzae isolates prevalent in India, was already cloned but its avirulent counterpart in the pathogen was not known. After decoding the whole genome of an avirulent isolate of M. oryzae, we predicted 11440 protein coding genes and then identified four candidate effector proteins which are exclusively expressed in the infectious structure, appresoria. In silico protein modeling followed by interaction analysis between Pi54 protein model and selected four candidate effector proteins models revealed that Mo-01947_9 protein model encoded by a gene located at chromosome 4 of M. oryzae, interacted best at the Leucine Rich Repeat domain of Pi54 protein model. Yeast-two-hybrid analysis showed that Mo-01947_9 protein physically interacts with Pi54 protein. Nicotiana benthamiana leaf infiltration assay confirmed induction of hypersensitive response in the presence of Pi54 gene in a heterologous system. Genetic complementation test also proved that Mo-01947_9 protein induces avirulence response in the pathogen in presence of Pi54 gene. Here, we report identification and cloning of a new fungal effector gene which interacts with blast resistance gene Pi54 in rice.